Comprehensive characterisation and analysis of PV module performance under real operating conditions. (8th December 2016) - Louwen, Atse; de Waal, Arjen C.; Schropp, Ruud E. I.; Faaij, André P. C.; van Sark, Wilfried G. J. H. M.
Abstract: The specifications of photovoltaic modules show performance under standard testing conditions (STC), but only limited information relating to performance at non‐STC conditions. While performance is affected by irradiance, temperature, spectral composition of irradiance, angle‐of‐incidence of the irradiance and other parameters, specifications only partly give detail to consumers or retailers about the effect of irradiance and temperature. In this study, we characterise and analyse the performance of eight different, commercially available photovoltaic modules. We establish the effect of four different parameters on module performance: irradiance, temperature, spectral composition of irradiance (via the parameter average photon energy) and angle‐of‐incidence, by performing linear and nonlinear optimisation of physical or empirical models. Furthermore, we characterise the operating conditions and analyse the seasonal and annual development and contribution of the four parameters to energy losses or gains relative to STC operating conditions. We show a comprehensive way of presenting the deviation of performance from STC, combining the variation in operating conditions and the resulting variation in performance. Our results show that some effects on performance are attributable to the semiconductor material used in the modules (spectral composition and temperature), while especially angle‐of‐incidence effects seem more related to the type of glass used on as the front cover of the module. Variation in irradiance and module temperature generally affect performance the strongest, resulting in a performance effect ranging from + 2.8% to − 3.2% and − 0.5% to − 2.2%, respectively. The combined effect of all parameters results in an annual yield deviation ranging from + 1.2% to − 5.9%. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : We characterised and analysed the effect of irradiance, temperature, spectrally distributed irradiance and angle‐of‐incidence on the outdoor performance of eight PV modules. Our results show that variation in irradiance and module temperature generally affect performance the strongest, resulting in a performance effect ranging from +2.8% to ‐3.2% and ‐0.5% to ‐2.2%, respectively. The combined effect of all parameters results in an annual yield deviation ranging from +1.2% to ‐5.9%.